THE EFFECT OF METACOGNITIVE STRATEGY ON STUDENTS’ READING COMPREHENSION AT SMK SWASTA YAPIM MEDAN - Ummi Kalsum Pasaribu (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
AbstractThe research objective was to find out the effect significantly from the implementation of the Metacognitive Strategy on reading comprehension of the students. The researchers formulated the research problem “Does Metacognitive strategy affect the students’ reading comprehension?”. In this research, The students of SMK Swasta Yapim Medan was chosen as the sample in this research.In this research,  researchers applied the experimental research. This research was done by applying the experimental group (applying the Metacognitive Strategy) and in the controlled group (without applying the Metacognitive Strategy) by using quantitative approach. The sample used by the researchers in this study was 72  students. 35 students were chosen as the sample in the experimental group. From the data it was known that the total score of the students in the experimental group after conducting the post-test was 2,714. After that the researchers found out that the students’ mean score was 77.54. There were 37 students in controlled group. The total scores after doing the post-test session in the controlled group was 2.526. The mean score of the students was 68.27. The researchers found out  the independent sample from the  t-test. After that the researchers found out that the t-table was lower than the t-test (t-table = 3.563 < t-test = 7.693). Meanwhile it was found out that the significance (p) was 0.001. The significance showed that 0.001 < 0.005 (p < 0,005). After conducting the research done by the researchers, it was known from the data that H1 can be accepted and H0 is rejected. The research findings were significant because p<0.005. From the data of the result as explained above, the researchers gave a conclusion that after applying the Metacognitive Strategy on the students’ reading comprehension, it had significantly affected the reading comprehension of the students.Key Words: The Effect, The Metacognitive Strategy, The Reading Comprehension